Religion, rights and secular society : European perspectives - Cumper, Peter; Lewis, Tom, 1966- (Cheltenham, UK : Edward Elgar, 2012)
This topical collection of chapters examines secular society and the legal protection of religion and belief across Europe, both in general and more nation-specific terms. The expectations of many that religion in modern Europe would be swept away by the powerful current of secularization have not been realised, and today few topics generate more controversy than the complex relationship between religious and secular values. The'religious/secular' relationship is examined in this book, which brings together scholars from different parts of Europe and beyond to provide insights into the methods by which religion and equivalent beliefs have been, and continue to be, protected in the legal systems and constitutions of European nations. The contributors' chapters reveal that the oft-tumultuous legacy of Europe's relationship with religion still resonates across a continent where legal, political and social contours have been powerfully shaped by faith and religious difference. Covering recent controversies such as the Islamic headscarf, and the presence of the crucifix in school class-rooms, this book will appeal to academics and students in law, human rights and the social sciences, as well as law and policy makers and NGOs in the field of human rights.
Introduction: Freedom of religion and belief : the contemporary context / Peter Cumper and Tom Lewis -- The Netherlands : neutral but no indifferent / Marjolein van den Brink and Titia Loenen -- Secularism and establishment in the United Kingdom / Peter W. Edge -- Law, religion and belief in Germany / Gerhard Robbers -- Religion in the constitutional order of the Republic of Ireland / Eoin Daly -- Religion and secular values in Spain : a long path to a real religious pluralism / Eugenia Relano Pastor -- The rise and contradictions of Italy as a secular state / Marco Ventura -- Religious freedom in a secular society : an analysis of the French approach to manifestation of beliefs in the public sphere / Sylvie Bacquet -- Secularism, law and religion within the Cypriot legal order / Achilles C. Emilianides -- The pendulum of church-state relations in Hungary / Renata Uitz -- Law, religion and belief in Slovakia, the Czech Republic and Poland / Michaela Moravcikova -- Human rights and religion in the Balkans / Julie Mertus -- Understanding religion in Europe : a continually evolving mosaic / Grace Davie -- Islam and secular values in Europe : from canon to chaos? / Jrgen S. Nielsen -- Legal considerations concerning new religious movements in the'new Europe' / James T. Richardson and Valerie A. Lykes.
Includes bibliographical references and index.
Keywords: Freedom of religion -- Europe; Secularism -- Europe; Religion and sociology -- Europe; Europe -- Religion